Fatigue failure monitoring of 316L stainless steel coupons using optical fibre based distributed strain sensing. (23rd September 2019) - De Pauw, Ben; Hinderdael, Michaël; Moonens, Marc; De Baere, Dieter; Geernaert, Thomas; Berghmans, Francis; Guillaume, Patrick
Abstract: We demonstrate the application of optical frequency domain reflectometry to detect, locate and track the propagation of fatigue cracks in simple beam-shaped stainless-steel specimens. To do so we recorded the strain distribution along the entire length of hot rolled and additively manufactured 316L steel specimens with a spatial resolution of 1 mm using an embedded optical fibre, and we evaluated fatigue induced damage under four-point bending load cycles. Our findings are threefold. First, we show that the onset of fatigue damage can be detected using our methodology based on a damage index adapted to optical frequency domain reflectometry measurements, which allows alerting for potential failure. We also show that our optical fibre mounting and embedding technique enables the fibre to survive critical failure of the steel specimen. In addition, we obtain strain profile measurements with a spatial resolution that allows linking the strain distribution with imperfections in the four-point bending set-up.